Build an Anticoruptive Generation - Aulia Ahsanal Rhamadina; M. Hafizh Syah Alam; Sekar Ayu Widhiastuti (Dinasti Research, 2020)
Corruption has become a classic case that is commonly encountered in everyday life. The perpetrators are no longer high-ranking officials in the elite, but have penetrated every level of society. This form of corruption is no longer just the theft of an extraordinary amount of money, but corruption is anything that is rotten and detrimental. Corruption has a massive impact on the sustainability of the country, including having an impact on the economy. If corruption continues, the motivation for economic growth will decrease or disappear from society and lead to widespread poverty. The construction of government facilities will also be slow and not optimal, the costs incurred are greater than the amount of money owned by the community so that these facilities cannot be enjoyed by them. Those who do not enjoy these facilities then look for ways to feel it by justifying various means including criminal acts including corruption. To eradicate corruption and its various impacts, the most effective thing is to change the mindset of all Indonesians. All citizens must be provided with insight into corruption so that they can understand the dangers of corruption and can adopt an anti-corruption attitude. This anti-corruption attitude will eventually form a generation with an anti-corruption culture.